Pojęcie działalności rolniczej w ustawach o podatku dochodowym od osób fizycznych i od osób prawnych - Bieluk, Jerzy (Wydawnictwo Naukowe UAM, 2008)
The deliberations presented in the paper focus on the definition of agricultural activity contained in the Personal and Company Income Tax Act. Polish law exempts agricultural activity from taxation, hence the importance for the tax payer of an accurate and precise definition of that activity. A detailed analysis of the above issue shows that certain formulations of the definition of agricultural activity are not only inaccurate, but often wrong. To give an example, there is no provision for the difference between breeding and raising, and mashrooms are listed as plants. It is therefore postulated that the existing definition should be redrafted, made more precise, and offer an accurate description o f activities exempted from taxation, made with regard to the existing regulations on the classification of goods and services.

L’obiettivo del saggio é la definizione di attivitá agricola prevista dalla legge sull’imposta sul reddito delle persone fisiche e delle persone giuridiche. Nel diritto polacco l’attivita agricola non é soggetta ad imposte sul reddito perció l’esatta determinazione di questa attivitá riveste grande importanza per il contribuente. L’approfondità analisi svolta conduce alla constatazione che i termini utilizzati nelle definizioni sono non solo imprecisi ma inducono anche in errore. Il legislatore, ad esempio, non distingue diversi tipi di allevamento ed include i funghi nelle piante. In conclusione l’Autore auspica il cambiamento delle definizioni analizzate, attraverso una stretta determinazione dei tipi di attività esclusi dalla tassazione, prendendo in considerazione le norme sulla classificazione delle merci e dei servizi.
The concept of agricultural activity in personal and company income tax act
La nozione di attivitá agricola nelle leggi sull'imposta sul reddito delle persone fisiche e delle persone giuridiche